THE MEANING OF KUFR IN THE BOOK OF HAMYĀN AL-ZĀD ILĀDĀR AL-MA'ĀD BY MUḤAMMAD BIN YŪSUF AL-IṬFISY - Huda, Syafiul; Sari, Maula; Fauziah, Cut (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2022)
Kafir in the Qur'an is not always associated with non-Muslim meanings. The meaning of Kafir in the Khawarij has various meanings. The Khawarij are followers of Ali bin Abi Talib who left the ranks due to disagreements with Ali, who accepted arbitration. Muhammad bin Yûsuf bin Îsâ bin Shâlih Ithfisiy is a khawarij figure who translated infidels in the book Hamyân al-Zâd ilâ Dâr al-Ma'âd. The method used in this research is qualitative and library-based research using the descriptive-analytical method, namely describing the book's object of study and then continuing to analyze the book. The purpose of this writing is to find out how Muhammad bin Yusuf al-Itfisiy views the deception of the meaning of kufr in his book. The results of this study are that Muhammad bin Yûsuf bin Îsâ bin Shâlih Ithfisy is not always kufr as kufr i'tiqad, which makes the perpetrators fight in hell. Muhammad bin Yûsuf bin Îsâ bin Shâlih Ithfisy divided what is meant by kufr as; 1) Lying in the name of Allah, 2) Not making revelation a law, 3) Apostasy, 4) Shirk, 5) Fighting the Believers.